Hubungan Gaya Belajar terhadap Hasil Belajar Kimia - Novela, Dalva; Irwandi, Dedi; Fairusi, Dila (Jurnal Riset Pendidikan Kimia (JRPK), 2022)
This purpose of this study is to determinethe relationship between learning styles with unimodal, bimodal, trimodal, and quadmodal student chemistry learning outcomes. The research subjects were 160 students of class XI IPA SMAN 4 South Tangerang. The research was conducted because each student has a different learning style and affects learning outcomes. The learning style used is VARK (Visual, Audio, Read and Kinesthetic). Based on the results of the reliminary analysis, students do not know their learning styles and there are still many students who have chemistry learning outcomes below the Minimum Completeness Criteria (KKM). The research method used is a correlational method with a cross sectional approach. Data were collected by using questionnaires and documentation techniques. Before the questionnaire was given to students, the validity and reliability were tested. The results of bivariate analysis using the contingency correlation test obtained p-value <0.05, so it can be concluded that there is a positive relationship between learning styles and chemistry learning outcomes for students of class XI MIPA SMAN 4 South Tangerang. The results of the univariate analysis showed that the most common learning styles were quadmodal (Visual, Audio, Read and Kinesthetic) 54 students (34%), unimodal 37 students (23%), trimodal 36 students (22%) and bimodal 33 students (21%). The results of learning chemistry obtained low scores as many as 89 students and high scores as many as 71 students. Keywords Learning Styles, Learning Outcomes, VARK